2017
DOI: 10.3389/fneur.2017.00166
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Outcomes among Stroke Survivors with Non-Valvular Atrial Fibrillation in China

Abstract: Atrial fibrillation (AF) significantly increases the risk of stroke and disease burden and is an established predictor of poor outcomes after stroke. However, data regarding sex differences in long-term outcomes following stroke in patients with AF are scarce. We thus aimed to assess these differences. We recruited 951 consecutive patients with acute ischemic stroke and non-valvular atrial fibrillation (NVAF) treated at three hospitals in Tianjin, China, from January 2006 to September 2014. Information regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…However, evidence from the literature was not consistent for either Western 44–47 or Asian countries. 11 , 48 , 49 Use of warfarin at discharge was less in women than in men in Get With The Guidelines-Stroke program 47 and the Swedish Risk-Stroke hospital-based registry, 44 whereas in studies from the Canadian stroke registry 45 and Medicare participants in Michigan, there were no sex differences. 46 This might be due to the fact that current evidence on appropriateness of anticoagulation is controversial in people with acute IS who have AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, evidence from the literature was not consistent for either Western 44–47 or Asian countries. 11 , 48 , 49 Use of warfarin at discharge was less in women than in men in Get With The Guidelines-Stroke program 47 and the Swedish Risk-Stroke hospital-based registry, 44 whereas in studies from the Canadian stroke registry 45 and Medicare participants in Michigan, there were no sex differences. 46 This might be due to the fact that current evidence on appropriateness of anticoagulation is controversial in people with acute IS who have AF.…”
Section: Discussionmentioning
confidence: 99%
“…However, observational evidence on how sex modifies the association between AF and outcomes is scarce. [8][9][10][11] In this study, we performed a systematic review of existing evidence and meta-analysis using individual participant data (IPD) of nine studies from the INSTRUCT. 11 Our aims were to outline the evidence for sex differences in disease profiles, management factors, and outcomes in participants with IS and AF.…”
mentioning
confidence: 99%
“…However, in another outpatient AF cohort, with a CHA 2 DS 2 -VASc score ≥2, women were associated with less frequent prescription of OAC [32]. Although the previous research suggested that female sex is not an independent risk factor of thromboembolism [33], women had poorer long-term outcomes among stroke survivors [34,35]. The extensive treatment gap in OAC use for stroke prevention remains in Chinese AF patients of both sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with men, women with AF also have greater risks of dependency and recurrence 36 months after a stroke after adjustment for stroke subtype, severity, and risk factors. 17 Moreover, not only do women with AF have a greater risk of stroke than men, the AF-related stroke is also more severe. 18 In one meta-analysis, the greater mortality after stroke in women was mostly attributable to their advanced age but greater stroke severity, greater pre-stroke functional limitations, and the presence of AF in women also contributed to the difference.…”
Section: Atrial Fibrillationmentioning
confidence: 99%